2021
DOI: 10.3390/nu13030935
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Formula Containing Synbiotics in Infants with Cow’s Milk Protein Allergy: A Systematic Review and Meta-Analysis

Abstract: Cow’s milk protein allergy (CMPA) is associated with dysbiosis of the infant gut microbiome, with allergic and immune development implications. Studies show benefits of combining synbiotics with hypoallergenic formulae, although evidence has never been systematically examined. This review identified seven publications of four randomised controlled trials comparing an amino acid formula (AAF) with an AAF containing synbiotics (AAF-Syn) in infants with CMPA (mean age 8.6 months; 68% male, mean intervention 27.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 50 publications
3
40
0
4
Order By: Relevance
“…The findings of this study are consistent with clinical trials of the only AAF-Syn currently available on prescription in the UK, which have shown significant reductions in infections, medications and hospital admissions when compared to AAF in infants with CMPA [20][21][22][23][24]. It is possible that the benefits seen are related to the clinical ef-fect of the specific synbiotic, which may have modified the dysbiotic gut microbiome of infants with CMPA, bringing it closer to that observed in studies of healthy breastfed infants [20][21][22][23]40,41]. The precise mechanism of the synbiotic effect remains unknown; however, the improvement of the gut microbiota profile through synbiotics may inhibit the growth of pathogenic organisms, thereby helping to reduce the incidence of infections [42] and associated healthcare usage in turn.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The findings of this study are consistent with clinical trials of the only AAF-Syn currently available on prescription in the UK, which have shown significant reductions in infections, medications and hospital admissions when compared to AAF in infants with CMPA [20][21][22][23][24]. It is possible that the benefits seen are related to the clinical ef-fect of the specific synbiotic, which may have modified the dysbiotic gut microbiome of infants with CMPA, bringing it closer to that observed in studies of healthy breastfed infants [20][21][22][23]40,41]. The precise mechanism of the synbiotic effect remains unknown; however, the improvement of the gut microbiota profile through synbiotics may inhibit the growth of pathogenic organisms, thereby helping to reduce the incidence of infections [42] and associated healthcare usage in turn.…”
Section: Discussionsupporting
confidence: 87%
“…The findings of this study are consistent with clinical trials of the only AAF-Syn currently available on prescription in the UK, which have shown significant reductions in infections, medications and hospital admissions when compared to AAF in infants with CMPA [ 20 , 21 , 22 , 23 , 24 ]. It is possible that the benefits seen are related to the clinical effect of the specific synbiotic, which may have modified the dysbiotic gut microbiome of infants with CMPA, bringing it closer to that observed in studies of healthy breastfed infants [ 20 , 21 , 22 , 23 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, their included literature are major low-quality evidence, reducing credibility with their results. Sorensen K [21] believed that compared with the amino acid formula alone, the hospitalization rate and overall drug use (including antimicrobial agents and antibiotics) of infants allergic to milk protein were lower in the amino acid formula containing synbiotics. However, there are some controversies between different researchers.…”
Section: Introductionmentioning
confidence: 99%